Proceedings of the 18th International Conference on Supporting Group Work 2014
DOI: 10.1145/2660398.2660416
|View full text |Cite
|
Sign up to set email alerts
|

Losing It Online

Abstract: Many people struggle with their weight and are turning to online communities for social and informational support. The aim of this study is to understand the issues commonly discussed in online weight loss communities. Through observation and content analysis of threads in one specific weight loss community, we identified 17 distinct categories discussed by the participants. We detail four categories specifically: Personal Experience, Consumption Choices, Dieting Strategy, and Exercise. Our analysis describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…For example, in a previous study of social-oriented chat on the Internet, nearly half (47%) of conversation was considered off-topic [6]. Additionally, keeping conversation on topic has been shown to be difficult even for highly focused discussion groups, such as those that discuss the Oklahoma City bombing [7] or health and fitness [8]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, in a previous study of social-oriented chat on the Internet, nearly half (47%) of conversation was considered off-topic [6]. Additionally, keeping conversation on topic has been shown to be difficult even for highly focused discussion groups, such as those that discuss the Oklahoma City bombing [7] or health and fitness [8]. …”
Section: Introductionmentioning
confidence: 99%
“…This is because all support that results in weight loss could be classified as such, according to Hwang et al (2010), who additionally noted that if instrumental social support is all the support tional coping relies on a perception of self-efficacy, i.e., a belief in one's ability to take control over the self and external factors (Bandura, 1997). Li et al (2014) observed that the social support received by individuals at the beginning of participation in an OHC increased their sensation of being able to control their weight. Nonetheless, there is as yet no conclusive evidence that social support is an independent factor in weight loss.…”
Section: Social Support Classification In Current Researchmentioning
confidence: 99%